Value of test latex fixation in diagnosing rheumatoid arthritis - Spilberg Kolker, Isaías (1964)
It is a known fact that the diagnosis of rheumatoid arthritis in clinical practice becomes often a complex and annoying problem. This truth was well illustrated when the American Association of rheumatoid thought it necessary that the manager committee drafting a Diagnostic Criteria (12, 5). This committee , headed by DI . Marion Rapes of Bastan , carried out his difficult task, but still felt compelled to register a set of 11 criteria , of which 5 could allow a "final diagnosis." Less certain diagnoses were allowed less criteria and categories of " Rheumatoid Arthritis Probable" and " Rheumatoid Arthritis Possible" revealed rather pathetically , weakness and lack of certainty in the diagnosis of rheumatic diseases in general and rheumatoid arthritis specifically . The Committee's efforts have been acknowledged to be of inestimable value, but leave no doubt of the great need to help laboratory diagnosis , tests that are simple , practicable and certain results at a significantly statistical level .